The complete writings essays and notes in original versions - Mondrian, Piet 1872-1944 (Primavera Pers, 2017)
From the beginning of 1914 until his death in 1944, Mondrian wrote more than a hundred essays on the subject of art and society. He wrote in Dutch, French and English, his choice of language often depending on his place of residence. All of Mondrian’s writings proclaim his conviction that art paves the way to a better society. Many of Mondrian's texts have been published, but the original versions were often translated, edited, and polished. This book aims to present the painter's words as he wrote them, going back to the original sources of all of Mondrian’s manuscripts, typescripts, and personal papers, published and unpublished, finished and unfinished - some only consisting of a few sentences, some of as much as 80 pages. In addition, the book includes introductory chapters, as well as a table for quick reference and a vocabulary of characteristic Mondrian terms. Louis Veen's compilation of Mondrian's original texts is not only a contribution to Mondrian research, but also a repository of knowledge regarding a small but essential part of the Dutch international heritage.